Agricultural Use of Untreated Urban Wastewater in Pakistan - Khalil, Samina; Kakar, Mehmood Khan (Asian Journal of Agriculture and Rural Development, 2011)
Untreated wastewater is used for irrigation in over 80% of all Pakistani communities with a population of over 10,000 inhabitants. The absence of a suitable alternative water source, wastewater’s high nutrient value, reliability, and its proximity to urban markets are the main reasons for its use. Two case studies in Pakistan studied the impact of untreated wastewater use on health, environment, and income. The results showed a high increase in hookworm infections among wastewater users and a clear over-application of nutrients through wastewater. Heavy metal accumulation in soil over a period of 30 years was minimal in Haroonabad, a small town with no industry, but showed initial signs of excess levels in soil and plant material in Faisalabad, a city with large-scale industry. The impact of wastewater irrigation on household income was considerable as wastewater farmers earned approximately US300/annum more than farmers using freshwater. Both case studies showed the importance of wastewater irrigation on local livelihoods. The lack of financial resources at municipal and provincial levels for wastewater treatment calls for other measures to reduce the negative impact of untreated wastewater use on health and environment, for example to manage groundwater, regular (canal) irrigation water, and wastewater conjunctively, and regular deworming treatment of those exposed to wastewater.